Marketing Public Relations Pemeritah Kabupaten Ponorogo dalam Meningkatkan Kunjungan Wisatawan Pasca Pandemi Covid 19 - Utomo, Bambang Setyo; Rukmini, Diah; Makhasi, Ghifari Yuristiadhi Masyhari; Maulana, Risal; Fairuzzabadi (Unitri Press, 2024)
Indonesia experienced a significant increase of 769.39% in foreign exchange revenue from the tourism sector compared to the previous year, which amounted to only US 0.49 billion. The demand for visits by foreign tourists to Indonesia during that year rose by 926%, reaching a total of 743 thousand visits. Ponorogo Regency is one of the Indonesian regencies that saw an increase in the number of tourists in 2022, with a total of 589,268 visitors during that year. This research aims to analyze the public relations marketing of Ponorogo Regency in enhancing tourist visits post the Covid-19 pandemic. This study employs a qualitative approach, specifically a case study. Research data were obtained through in-depth interviews with three informants from the Department of Culture, Tourism, Youth, and Sports in Ponorogo, non-participatory observation, and documentation. The findings of the research indicate that to increase tourist visits post-Covid-19, the Ponorogo Regency government, through the Department of Culture, Tourism, Youth, and Sports office, utilizes a public relations marketing strategy consisting of three approaches: pull, push, and pass. The pull strategy involves advertising, sales promotion, and social media publicity. The push strategy employs personal selling and direct marketing. Meanwhile, the pass strategy includes organizing events, providing sponsorships, and building good relationships with stakeholders. Abstrak Tahun 2022 pendapatan devisa dari sektor pariwisata Indonesia mengalami kenaikan hingga 769,39% dibandingkan tahun sebelumnya yang hanya mencapai US 0,49 miliar. Permintaan kunjungan wisatawan asing ke Indonesia pada tahun itu meningkat sebesar 926% dengan jumlah kunjungan mencapai 743 ribu. Kabupaten Ponorogo menjadi salah satu kabupten di Indonesia yang mengalami peningkatan jumlah wisatawan pada tahun 2022. Jumlah wisatawan yang berkunjung ke Ponorogo pada tahun itu mencapai 589.268 orang. Penelitian ini bertujuan untuk menganalisis marketing public relations Kabupaten Ponorogo dalam meningkatkan kunjungan wisatawan pasca pandemi covid 19. Untuk menggali data secara mendalam penelitian ini menggunakan pendekatan kualitatif dengan jenisnya studi kasus. Data penelitian diperoleh melalui wawancara mendalam dengan tiga informan dari Dinas Kebudayaan Pariwisata, Pemuda dan Olahraga Kabupaten Ponorogo, observasi non partisipatif, dan dokumentasi. Hasil penelitian menunjukkan bahwa untuk meningkatkan kunjugan wisatawan pasca Covid 19 pemerintah Kabupaten Ponorogo melalui DISBUDPARPORA menggunakan marketing public relations yang terdiri dari tiga strategi yaitu pull, push, dan pass. Strategi pull dengan menggunakan periklanan, sales promotion dan publikasi di media sosial. Untuk strategi push dengan menggunakan personal selling dan direct marketing. Sedangkan strategi pass dengan menyelenggarakan event, memberikan sponsorship, dan membangun hubungan baik dengan para stakeholder.